Fenomena Penyalahgunaan NAPZA Di Kalangan Remaja Ditinjau Dari Teori Interaksionisme Simbolik Di Kabupaten Jember (The Phenomenon of Substance Abuse among Adolescents Based on Symbolic Interactionism Theory in Jember Regency ) - Hesty Damayanti Saleh; Dewi Rokhmah; Iken Nafikadini (Pustaka Kesehatan, 2014)
Substance abuse in adolescent is one of the big threat in Indonesia, in Jember regency from 2013-2014, there are 28 adolescents abuse the substance, this case was so dangerous for the future of adolescents. This research design used qualitative design with phenomenon approach and resource triangulation technique. The purpose of this research was to analysis the phenomenon of substance abuse amongst adolescents based on symbolic interactionism theory in jember regency. The informant got by purposive and obtained 4 informants. Based on the research result showed that the informants age are 22-23 years old. They began to abuse some drugs in junior high school. The main informants use cannabis. The informants use special language to communicate with others who also abuse substance. They have positive self concept before abuse substance and negative self concept after become substance abuser. substance abuse can influence the social interaction especially with their friends and society in around them. Most of the informants family’s didn’t know that informants as substance abuser, but in other hand most of their girl friend known that informants as substance abuser. Based on the research, it is necessary to give information about the dangerous of substance abuse for adolescent by increasing the role of adolescent in PIK adolescent and health school center. Keywords: Substance abuse, Adolescent, Symbolic Interactionism Theory